In for a penny, in for a pound? - Scheidt, Stefan (2018)
Scheidt, S., Gelhard, C., Strotzer, J., & Henseler, J. (2018). In for a penny, in for a pound? Exploring mutual endorsement effects between celebrity CEOs and corporate brands. Journal of Product and Brand Management, 27(2), 203-220. DOI: 10.1108/JPBM-07-2016-1265